PERANCANGAN SISTEM APLIKASI BIAYA SERVICE PADA PT. ALFA SCORPII BRAHRANG UNTUK MEMPERMUDAH SISTEM PELAPORAN - Syahputri, Heni; Andriansyah, M Juli; Sihombing, Anton; Novriyenni, Novriyenni (STMIK Kaputama, 2017)
In the data processing system service motorcycle at PT. Alpha Scorpii Brahrang they often appear several errors in the processing of data reporting service for not using a computerized system. This can result in data processing becomes less effective. From the analysis that has been done at PT. Alpha Scorpii, then designed a system application that uses a programming language VB.Net 2010, which can store data and be able to overcome the delay in presentation time data reporting service fee.With a system of new applications and system design writer for this can help speed up the officers in the reporting process cost service, where data received will be more efficient and the data will be properly maintained and to facilitate managers in viewing report service costs and promote PT , Alpha Scorpii Brahrang.